2001
DOI: 10.1034/j.1600-0560.2001.028006298.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of cyclooxygenase‐2 in skin cancers

Abstract: These results indicate that the intensity of COX-2 staining and its heterogeneous distribution are related to the degree of cellular differentiation and the various phenotypes of tumor cells, but the extent of COX-2 staining did not correlate with the degree of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 20 publications
(27 reference statements)
8
50
1
1
Order By: Relevance
“…Such a result is in general agreement with earlier reports of other groups which have described very low COX-2 expression in most BCCs (undetectable in others) [39,40] or undetectable COX-2 expression in the majority of cases with weak expression found only in a small fraction of the lesions investigated [34,35,37,41]. Taking into account the good reproducibility of our results for a large number of samples of normal skin, and the consistency of the results obtained for BCCs, it seems reasonable to conclude that the reports of undetectable COX-2 expression in smaller or larger fractions of the BCCs examined in earlier studies reflected insufficient sensitivity of the COX-2 detection rather than a lack of the protein in the BCC cells.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Such a result is in general agreement with earlier reports of other groups which have described very low COX-2 expression in most BCCs (undetectable in others) [39,40] or undetectable COX-2 expression in the majority of cases with weak expression found only in a small fraction of the lesions investigated [34,35,37,41]. Taking into account the good reproducibility of our results for a large number of samples of normal skin, and the consistency of the results obtained for BCCs, it seems reasonable to conclude that the reports of undetectable COX-2 expression in smaller or larger fractions of the BCCs examined in earlier studies reflected insufficient sensitivity of the COX-2 detection rather than a lack of the protein in the BCC cells.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the precancerous lesions and SCCs expressed COX-2 at a similar level. Although some authors have reported stronger COX-2 staining in SCCs compared to KA [35,36] more groups have described similar (or only slightly higher) COX-2 expression in SCCs compared to precancerous lesions like AK, KA and BD [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and 88% in BD, 50 and 83% in AK and it was of 25% in benign papillomas Kagoura et al, 2001;Kim et al, 2006). COX-2 over-expression has also been determined in mice models of skin abnormalities, such as hyperplasia of the skin, benign papillomas and SCC -resulting from UV chronic irradiation-.…”
Section: Epidemiological Datamentioning
confidence: 99%